PEMODELAN SPASIAL KERAWANAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) MENGGUNAKAN LOGIKA FUZZY DI KABUPATEN KUDUS - Fariz, Trida Ridho (Jurnal Geografi, 2017)
Dengue Fever is a tropical infectious diseases which often cause epidemic in Indonesia. Kudus Regency is one of the area which every years increased extremly Dengue Fever distribution. The one of act for prevention and controlling of Dengue Fever is build a hazard mapping of this disease. The purpose of this research is build a spatial modelling of Dengue Fever hazard with fuzzy logic.This modeling is built from determinant hazard level indicators of Dengue Fever like rainfall index, settlement density, land elevation and water supply. Analisys used fuzzyfication then fuzzy overlay with operators are: AND, OR, SUM, PRODUCT, GAMMA-0,5 and GAMMA-09. The best result is a Overlay PRODUCT with correlation value of 0,57 and defuzzyfication area with high level of Dengue Fever hazard are Jati District, Kudus District and partially of Bae District dan Kaliwungu District.Conclussion from this research, fuzzy logic is pretty good for build spatial modelling of Dengue Fever hazard in Kudus Regency, other than that model still needs to be tested accuracy in modelling of Dengue Fever hazard in other places.